Impact of active night population and leakage exponent on leakage estimation in developing countries. Issue 1 (13th December 2021) - Amoatey, Peace Korshiwor; Obiri-Yeboah, Abena Agyeiwaa; Akosah-Kusi, Maxwell
Abstract: Methods for network leakage estimation include water balance, component analysis and minimum night flow (MNF) methods, the latter of which involves subtracting the customer night use (QCNU ) from night leakage and multiplying by the hour day factor (HDF). QCNU and HDF respectively depend on Active Night Population (ANP) and leakage exponent (N1). In most developing countries, these parameters are assumed in the MNF method, thus introducing errors which makes setting realistic leakage reduction targets and key performance indicators (KPI) problematic. In this study, QCNU and HDF were evaluated by determining the relative error associated with ANP and N1 to establish localized rates for accurately estimating leakage in water networks. Between 7 and 11% relative error was associated with every 1% higher or lower ANP while up to 4% relative error was observed for every step considered. A linear relationship exists between the relative error associated with both and ANP although that of ANP is twice as high as This has technical implications for setting water loss reduction targets and investing in the water infrastructure. It is recommended that water utilities must establish localized ANP and values for accurate leakage estimation in water networks. HIGHLIGHTS: Customer night use and Hour-day factor, which respectively depend on active night population and leakage exponent, are key parameters for use in the minimum night flow method. Active night population rate and leakage exponents will enhance the accuracy of the amount of leakage estimated. Key Performance indicators computed, realistic targets set and infrastructure investments for water loss reduction ensured. Graphical Abstract